Conservation Behavior in the Agricultural Societies of Java - Wijaya, R. Pasifikus Christa; Faturochman, Faturochman (Faculty of Psychology, Universitas Gadjah Mada, 2019)
This research aimed to gain a deeper understanding of the conservation behavior in the context of the Java community. A deep exploration was conducted on the ecological value model, dynamics of ecological value activation, social attachment bias and collective efficacy in the development of the conservational movement in Menoreh hills. Approach to ethno-phenomenology was made towards five subjects who were chosen by purposive sampling technique. The results showed several conclusions. Harmony of life is the main reason that animates the conservation practice. Peace was translated as biospheric values namely, niteni (pay attention carefully), gemati (nurture with affection) and altruistic value nguri-uri (maintaining a legacy for the next generation). Culturally, the agents who were able to revive the conservation movement has high participation in community activities (akeh srawung), trusted as the source of information and had networked with local policy figure (key figure) as the head of the village and the regent. Without the support of a key figure, collective efficacy will weaken due to the loss of access to the collective agreement and conformity of the conservation movement.